The Contest of Judicial Rationality: An Examination of Judges' Considerations in PTUN Cases No. 21/G/2022/PTUN.GTO and 19/B/2023/PT.TUN.MDO - Bahutala, Andris E.; Wantu, Fence M.; Ahmad, Ahmad (Universitas Negeri Gorontalo, 2025)
This study examines the contestation of judicial rationality in the resolution of civil servant (ASN) disciplinary disputes at two levels of administrative court, namely the Gorontalo Administrative Court (PTUN Gorontalo) and the Manado Administrative Court (PT.TUN Manado), focusing on cases No. 21/G/2022/PTUN.GTO and No. 19/B/2023/PT.TUN.MDO. Using a juridical-normative approach and case analysis, the study highlights the fundamental differences in the reasoning of first-instance judges, who emphasize adherence to formal procedures and the protection of individual ASN rights, compared to the approach of appellate judges, who prioritize substantive justice, public utility, and proportionality of sanctions to maintain bureaucratic integrity. The findings indicate that judicial interpretation of administrative law is strongly influenced by the concrete context of the case, the judges' backgrounds, and their orientation towards justice, leading to disparities in decisions that result in legal uncertainty and inadequate protection for ASNs. The study concludes that standardizing judicial reasoning through technical guidelines that integrate procedural and substantive justice principles is necessary, alongside strengthening the training and mentoring of judges to ensure consistent, fair decisions that are focused on improving bureaucratic governance. Recommendations are made to promote the establishment of a national database of ASN disciplinary decisions, cross-agency collaboration, and regular regulatory evaluations to make the administrative justice system more accountable and responsive to individual rights and public interests.